Green Analysis by Eco-scale Assessment for Quality Control of Azithromycin Tablets - Sinzervinch, Aline; Kogawa, Ana Carolina (Current Pharmaceutical Analysis, 2024)
BackgroundAzithromycin (AZT), an antimicrobial, despite having a monograph in official compendiums and some methods available in the literature, there is still a demand for eco-efficient methods, which include green analytical chemistry.ObjectivesThis study aimed to develop and validate a green spectrophotometric method for quantifying AZT tablets.MethodsPurified water and ethanol (90:10, v/v) and sulfuric acid 20% as a diluent and reagent, respectively, quartz cubette and 482 nm were used. The Eco-Scale Assessment (ESA) tool was used to evaluate the greenness of the proposed analytical method.ResultsThe proposed method was linear (20-70 µg mL-1 with a correlation coefficient of 0.9984), precise (RSD < 5%), selective by sample adjuvants, exact (100.46%), and robust against changes in acid proportion and wavelength. The ESA calculation was 85 points.ConclusionThe proposed method can be classified as an excellent green alternative to quantify AZT in tablets, in accordance with ESA.
Keywords: eco-scale assessment